Study in Indonesia: A New Perspective and Conceptual Framework for Increasing Customer E-Loyalty in E-Commerce - Eko Yuliawan; Mohammad Hamsal; Asnan Furinto; Rano Kartono (Journal of International Conference Proceedings, 2022)
This paper aims to provide a new conceptual framework perspective on how to boost customer e-loyalty in e-commerce. A literature review was performed in this study as an approach, the findings of this study contribute to the development of a conceptual framework for the factors that influence customer e-loyalty in e-commerce. This study offers seven research propositions as well as recommendations for future empirical research.Â Keywords: E-Service Quality, E-Recovery Service Quality, E-Trust, Perceived Enjoyment, E-Satisfaction-E-Loyalty